Design and development of capacitance based moisture measurement for grains. (2021) - Tinna, Arpit; Parmar, Nitesh; Bagla, Suraj; Goyal, Deepam; Senthil, V.
Abstract: Moisture plays a vital role in several aspects of storage, drying, processing of grains and to understand the properties of grains. In general, the moisture content in grains can be measured by direct and indirect methods. Schematically, the former includes gravimetric method whereas the latter comprises resistance, capacitance-based measurements. Also, the direct method has been proved to be more time-consuming in comparison to the indirect one. Apart from these methods, calorimetry based measurements, the Karl Fischer method, is restricted to their laboratory research purpose and is not being used in industries for real-time measurement. In this article, a new capacitance-based method for grain moisture measurement has been developed which relies upon the integration of IC555 timer. The experimental findings revealed that with an increase in mean frequency value from 343310.04 to 355271.16, the capacitance values dropped from 2.03446369 to 1.9678978 respectively and these results have proved to be economical and reliable in terms of providing a promising relationship between the grain moisture content and capacitance of the circuit in further investigation. The effectiveness of the developed method was corroborated by comparing the results with the resistance measurement method.